Disruption of cardio-pulmonary coupling in myopathies: Pathophysiological and mechanistic characterization with special emphasis on nemaline myopathy - Ronderos-Botero, Diana Maria; Dileep, Arundhati; Yapor, Laura; Singhal, Ravish (Frontiers in Cardiovascular Medicine, 2022)
The heart and lung are in continuous reciprocal interaction that creates a functional and anatomical reserve referred to as cardiopulmonary coupling (CPC). Disruption of CPC can occur due to various different cardiac or pulmonary pathologies but also can occur in patients with myopathies. Nemaline myopathy (NM) is a skeletal muscle heterogeneous disorder due to contractile proteins’ gene mutations which impacts lung and cardiac mechanics and thus is expected to adversely affect CPC in a complex manner. We present a case of NM and we review the literature of cardiac and pulmonary effects of myopathy-related disruption of CPC.